On The Material And Spiritual History Of Khorazm During The Ancient Age (Eurasian Journal of History, Geography and Economics, 2024)
This article discusses the material and cultural history of Khorezm on the basis of materials obtained from written sources and as a result of archaeological findings conducted in the region.